Analisis Manajemen Pengelolaan Bisnis Budidaya Magot Perspektif Ekonomi Islam - Zainuddin, Zainuddin; Dzikrulloh, Dzikrulloh (INSTITUT AGAMA ISLAM TARBIYATUT THOLABAH LAMONGAN, INDONESIA, 2020)
Magot is a maggot produced from black fly eggs (BSF) which is very active in breaking down organic waste and has a high protein content that can be utilized properly for animal feed etc. magot is the main attraction for business actors. It becomes very important to examine how the management of the business is managed. Therefore, the author takes the title